Decrease in Intramuscular Levels of Phosphatidylethanolamine Bearing Arachidonic Acid During Postmortem Aging Depends on Meat Cuts and Breed. Issue 5 (3rd April 2019) - Yamashita, Shinji; Shimada, Kenichiro; Sakurai, Riho; Yasuda, Nohara; Oikawa, Nayoko; Kamiyoshihara, Reina; Otoki, Yurika; Nakagawa, Kiyotaka; Miyazawa, Teruo; Kinoshita, Mikio
Abstract : The intramuscular phospholipid (PL) level is reported to decrease upon postmortem aging of beef, pork, and chicken, and the change affects meat qualities (e.g., myofibrillar fragmentation and drip loss); however, there is still little information on the effect of muscle position and breed on PL compositions. A preliminary study is performed to investigate the effect of intramuscular PL composition on postmortem aging of beef and venison. Loin and round parts of beef and venison are kept at 4 °C for 28 postmortem days to elucidate the maximum effect of meat aging. The arachidonic acid (20:4n‐6) content in PL decreases in round meat during postmortem aging, while the PL 20:4n‐6 content is not affected in loin meat. The PL molecular species analysis reveals that such content reduction is consistent with decreases in phosphatidylethanolamine (PtdEtn) levels, especially that bearing 20:4n‐6. In addition, the content reduction by aging is affected by the meat cuts and the breed. These results suggest that PL variation depends on meat cuts and breed, and the release of 20:4n‐6 from PL has a considerable influence on meat qualities owing to the high reactivity of the polyunsaturated chain. The present results will enable eventual improvement of the taste, smell, and texture of meat during postmortem aging. Practical Applications : This preliminary study investigates the changes in intramuscular PL composition in beef and venison after postmortem aging. Consequently, PL variation depends on meat cuts and may be induced potentially owing to activity of cytosolic phospholipase A2 . Meat properties (e.g., drip, flavor, and taste) are considered as affected by the PL hydrolysis and the 20:4n‐6 release. Therefore, monitoring of variation of PL species might be useful to estimate the condition of meat quality by postmortem aging. Our preliminary study investigates the changes in intramuscular phospholipid (PL) composition in beef and venison after postmortem aging. Postmortem aging decreases the phospholipid levels in meats. The 20:4n‐6 is released from the meat phospholipid during postmortem aging. The two above‐mentioned are considered due to hydrolyzation of the diacylglycerophospholipids in meats. The hydrolysis of phospholipid may depend on meat cuts and breed. Abstract : Our preliminary study investigates the changes in intramuscular phospholipid (PL) composition in beef and venison after postmortem aging. Postmortem aging decreases the phospholipid levels in meats. The 20:4n‐6 is released from the meat phospholipid during postmortem aging. The two above‐mentioned are considered due to hydrolyzation of the diacylglycerophospholipids in meats. The hydrolysis of phospholipid may depend on meat cuts and breed.